Diethylnitrosamine Increases Proliferation in Early Stages of Hepatic Carcinogenesis in Insulin-Treated Type 1 Diabetic Mice - Arboatti, Ainelén Soledad (2018)
Diethylnitrosamine (DEN) induces hepatocarcinogenesis, increasing mitotic hepatocytes and leading to chronic inflammation. In addition, type 1 diabetes mellitus (T1DM) is also characterized by a proinflammatory state and by requiring insulin exogenous treatment. Given the association of diabetes, insulin treatment, and cell proliferation, our specific goal was to determine whether the liver in the diabetic state presents a greater response to DEN-induced cell cycle alteration, which is essential for the malignant transformation. Male C57BL/6 mice (four-week-old) were divided into 4 groups: C, C + DEN, T1DM, and T1DM + DEN. Mice were euthanized ten weeks after DEN injection. DEN per se produced an increase in liver lipid peroxidation levels. Besides, in T1DM + DEN, we found a greater increase in the proliferation index, in comparison with C + DEN. These results are in agreement with the increased expression observed in cell cycle progression markers: cyclin D1 and E1. In addition, a proapoptotic factor, such as activated caspase-3, evidenced a decrease in T1DM + DEN, while the Vascular Endothelial Growth Factor (VEGF) and the protooncogene p53 showed a higher increase with respect to C + DEN. Overall, the results allow us to highlight a major DEN response in T1DM, which may explain in part the greater predisposition to the development of hepatocarcinoma (HCC) during the diabetic state.